Load Aware Channel-Width Assignments in Wireless LANs - Bahl, Victor; Chandra, Ranveer; Moscibroda, Thomas; Wu, Yunnan; Yuan, Yuan (2007)
Measurements studies show that there exist large spatial and temporal fluctuations in the traffic load handled by different access points in Wireless LANs. In order to alleviate this problem, researchers have proposed various load-balancing techniques based for instance on channel assignment, power control, or client allocation. Fundamentally, however, assigning each AP the same amount of bandwidth (one channel) can inevitably lead to inefficient usage of the spectrum. In this work, we address the problem by adaptively tuning a radio parameter that has so far been largely untouched in Wireless LAN networks: the channel-width. Particularly, we show that a significant improvement in network capacity and per-client fairness can be achieved if the channel-widths at different APs are made a function of the traffic load. We propose the use of dynamic-width channels, where every AP adjusts its center-frequency and channel width to match its current traffic load. Our techniques are made possible by recent advances in radio hardware design and do not require changes in current hardware. We demonstrate the effectiveness of our scheme through analysis and simulations using real-world scenarios.